Pengembangan Instrumen Keterampilan Pengendalian Emosi Pada Siswa Sekolah Dasar - Primadoni, Ade Bagus; Kusumawati, Dian (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study aims to develop a valid and reliable emotional control skills instrument for elementary school students. Emotional control is one of the essential skills in supporting children's learning success and social adaptation. The method used is research and development (R&D) with the Borg & Gall model, which includes the stages of preliminary study, instrument design, expert validation, limited testing, and field testing. The test subjects consisted of 30 fifth-grade elementary school students. The developed instrument consisted of 40 statements, of which 25 were found to be valid based on indicators of children's emotional control skills. Data were collected through questionnaires distributed to students and assessed using Cronbach's Alpha internal reliability test. The analysis results showed a Cronbach's Alpha value of 0.846, which is higher than (Î± > 0.6), indicating that the instrument has a high level of reliability. These findings reinforce that the instrument is suitable for use as an assessment tool to measure emotional control skills consistently and accurately in elementary school students. This study contributes to providing an applicable and contextual psychopedagogical measurement tool for the elementary education environment.